2007
DOI: 10.1016/j.brainres.2006.11.059
|View full text |Cite
|
Sign up to set email alerts
|

Chronic cocaine exposure in the SCID mouse model of HIV encephalitis

Abstract: Clinical and preclinical evidence suggests that cocaine exposure hastens progression of the HIV disease process. An established active, euphoric dose of cocaine (20 mg/kg) was administered to SCID mice according to a regimen consistent with exposure to the drug by cocaine-abusing HIVinfected patients to determine the effects of cocaine on four previously established pathological characteristics of HIV encephalitis: cognitive deficits, fatigue, astrogliosis, and microgliosis. Mice were intracranially inoculated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“…The results of the present study are also consistent with studies in the SCID-HIV model of AIDS, which indicated that cocaine did not exacerbate known motor and cognitive impairments caused by HIV (Griffin et al 2007). As reported previously, there was a significant correlation between impairment on the BMS task and APP accumulation in the corpus collosum (Weed et al 2003).…”
Section: Discussionsupporting
confidence: 90%
“…The results of the present study are also consistent with studies in the SCID-HIV model of AIDS, which indicated that cocaine did not exacerbate known motor and cognitive impairments caused by HIV (Griffin et al 2007). As reported previously, there was a significant correlation between impairment on the BMS task and APP accumulation in the corpus collosum (Weed et al 2003).…”
Section: Discussionsupporting
confidence: 90%
“…The brains of these SCID mice inoculated intracerebrally with HIV-infected human monocytes characteristically have HIV-infected human mononuclear phagocytes, multinucleated giant cells, increased human cytokine expression, and increased levels of astrocytes and microglia, most notably, astrogliosis (Tyor 1993, Persidsky 1996, Griffin 2004, Cook 2005, Griffin 2007. Furthermore, these infected SCID mice with characteristic HIVE neuropathology have cognitive deficits (Avgeropoulos 1998, Griffin 2004, Griffin 2007. The pathological and cognitive deficits in HIVE SCID mice are similar to those seen in humans with HAD.…”
Section: Introductionmentioning
confidence: 78%
“…A SCID mouse model of HIVE was developed to help further elucidate the pathogenesis of HAD (Tyor 1993, Persidsky 1996, Avgeropoulos 1998, Griffin 2004, Cook 2005. The brains of these SCID mice inoculated intracerebrally with HIV-infected human monocytes characteristically have HIV-infected human mononuclear phagocytes, multinucleated giant cells, increased human cytokine expression, and increased levels of astrocytes and microglia, most notably, astrogliosis (Tyor 1993, Persidsky 1996, Griffin 2004, Cook 2005, Griffin 2007. Furthermore, these infected SCID mice with characteristic HIVE neuropathology have cognitive deficits (Avgeropoulos 1998, Griffin 2004, Griffin 2007.…”
Section: Introductionmentioning
confidence: 99%
“…Proteomics analyses have revealed the enhancement of HIV-replication in normal human astrocytes after exposure to cocaine (Reynolds et al 2006). The interaction of HIV-1 with cocaine has also been evaluated using an in vivo mouse model with severe combined immunodeficiency which revealed that cocaine enhances the HIV-replication (Roth et al 2002; Griffin et al 2007). …”
Section: Introductionmentioning
confidence: 99%